Penerapan Media Ular Tangga Materi Sikap Menaati Aturan untuk Meningkatkan Motivasi Belajar Literasi Siswa Kelas II SDN Panggunglor Semarang - Nurwulan, Devi Ayuk; Listyarini, Ikha; Prasetiawati, Catur; Saputra, Henry Januar (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research aims to analyze the influence of the use of Snakes and Ladders media as material about obeying rules (Variable The research design uses a simple paradigm research design with one independent variable and one dependent variable. Data obtained through a questionnaire with Likert scale calculations. The location of this research will be carried out in class II of SDN Panggung Lor Semarang. The sample in this study was 25 class II students using saturated sampling techniques. The data analysis technique used in this research starts from descriptive analysis and the data analysis technique used in this research starts from descriptive analysis. The results of this research show the results of a simple linear regression test with a value of tcount of 4.987 > ttable 2.069 (0.25 : 23), so it can be concluded that the application of Snakes and Ladders media material on the attitude of obeying the rules (Variable X) on students' motivation to learn literacy (Variable Y ) second grade students at SDN Panggunglor. Based on the research results, it can be concluded that the application of the Snakes and Ladders game media with material about obeying the rules has a significant positive impact on students' motivation in learning literacy.